Group of Housings and Public Space in San Gabriel Alto. Project Strategies to Urbanize the Hillside - Cieza-de-León-Valdivia, Rodrigo (Universidad de Lima. Carrera de Arquitectura, 2017)
This article describes a project of housings and public spaces in Villa María del Triunfo, in Lima, Peru. The description of the project is based on four design strategies that try to fit correctly to its environmental condition, thus it intends to contribute to the search of a project model appropriate for the hillsides of Metropolitan Lima where the informal settlements are. As an introduction, the informal settlements will be questioned, the value of a building will be set out and the work of an urban development plan will be emphasized.